Indikator Makro Ekonomi dan Pengaruhnya pada Indeks Saham Sektor Infrastruktur Indonesia - Meidiaswati, Harlina; Kusumawati, Nunik Dwi (Journal of Infrastructure Policy and Management (JIPM), 2023)
This research examines the influence of macroeconomics as measured by exchange rates, interest rates and inflation on the movement of the Infrastructure industry stock indeX in Indonesia (IDXINFRA). This research uses secondary data: infrastructure industry sector stock index, Indonesian bank interest rates, inflation, and exchange rates taken monthly for an observation period from January 2020 to October 2023, resulting 34 data. Time series data analysis was carried out using a multiple linear regression approach. The test results show that partially, the exchange rate has a positive effect and interest rates have a negative effect, while inflation has no effect. Further research can be carried out by considering micro factors in addition to macro factors which are proven to influence the movement of the Infrastructure Industry Stock Indeks (IDXINFRA).